2012
DOI: 10.1002/bjs.8738
|View full text |Cite
|
Sign up to set email alerts
|

Rapid on-site evaluation of axillary fine-needle aspiration cytology in breast cancer

Abstract: AUS with FNAC provided accurate preoperative staging of the axilla for metastatic breast disease and avoided unnecessary sentinel lymph node mapping. The introduction of ROSE ensured the efficiency of AUS and FNAC.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

1
14
1
1

Year Published

2013
2013
2022
2022

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 20 publications
(17 citation statements)
references
References 23 publications
1
14
1
1
Order By: Relevance
“…However, we found an inadequate sampling rate of 19.7% (18/91), and these cases were considered nondiagnostic. O'Leary et al [18] evaluated 152 axillary FNA cases and found 80/83 cases to be adequate with ROSE versus 54/69 adequate cases without ROSE. The nondiagnostic/inadequate sampling rate could possibly be reduced by ROSE of the cytologic material by a cytopathologist [17].…”
Section: Discussionmentioning
confidence: 99%
“…However, we found an inadequate sampling rate of 19.7% (18/91), and these cases were considered nondiagnostic. O'Leary et al [18] evaluated 152 axillary FNA cases and found 80/83 cases to be adequate with ROSE versus 54/69 adequate cases without ROSE. The nondiagnostic/inadequate sampling rate could possibly be reduced by ROSE of the cytologic material by a cytopathologist [17].…”
Section: Discussionmentioning
confidence: 99%
“…The technique has been shown to have good diagnostic accuracy, with a sensitivity of 65–99% and a specificity of 80–100% [21]; to detect ≥3 positive nodes, sensitivity was 44.8%, specificity 95.7%, PPV 58.1%, and NPV 92.9% [20]. Rapid on-site evaluation of ALNs in aspirated specimens has been shown to be diagnostically helpful [21, 22]. USG-FNAC of ALNs has been conducted in several institutions reporting a sensitivity, specificity, PPV, and NPV of 86.4, 100, 100, and 67%, respectively [23], with an accuracy of 79%.…”
Section: Discussionmentioning
confidence: 99%
“…One possible compromise is for the radiologists to perform FNA without ROSE. Studies have shown that diagnostic accuracy of FNA improves with ROSE, 12,13 however, while it may be helpful in improving the positivity rate, it adds time to cases and is technically unnecessary for axillary lymph node evaluation, since NCCN guidelines recommend sentinel lymph node sampling for clinically suspicious lymph nodes that are negative by FNA or core needle biopsy. 2 To entertain this compromise, we are now collaborating with our radiologists on a prospective study to compare core biopsy to FNA using ThinPrep only, with the option to perform cell blocks on certain cases, such as known lobular carcinoma, to reduce false positives.…”
mentioning
confidence: 98%